(untitled) (PANGEEA, 2025)
The influence of relief and zonals , axis’’ tips in the spatial geographic organising and territorial development of Alba County. Geographical background of Alba County is very complex, offering a different geographic potential. This potential is given by the position of the areas and the specific of the human locations system which influences the development of the district. The geographical axis may be understood as being territorial complexes as the lines of force with space and temporal character in a area with different geomorfic conformation and dimensions accorded in the polarisation of the components.